To solve the equation, first find a common denominator for both fractions on each side of the equation. We can use x + 4 and x + 3 as the common denominator.
(-2)/(x + 4) = 4/(x + 3)
Multiply both sides by (x + 4)(x + 3) to get rid of the denominators:
-2(x + 3) = 4(x + 4)
Expand and simplify:
-2x - 6 = 4x + 16
-6 - 16 = 4x + 2x
-22 = 6x
x = -22/6
x = -11/3
So, the correct answer is:
D. negative eleven over three
Now, check the solution:
Replace x with -11/3 in the original equation:
(-2)/(-11/3 + 4) = 4/(-11/3 + 3)
(-2)/(-11/3 + 12/3) = 4/(-11/3 + 9/3)
(-2)/(1/3) = 4/(-2/3)
-6 = -6
The solution checks out.
Solve the equation. Check the solution.
negative two over x plus four equals four over x plus three
A.negative thirteen over six
B.–11
C.negative eight over three
D.negative eleven over three
1 answer